Cardiovascular Involvement in Behçet’s Disease - Tolga AKSU; Erdem GÜLER; Nurcan ARAT; Ali ZORLU; Birhan YILMAZ; Ümit GÜRAY; Omaç TÜFEKÇİOĞLU and Halil KISACIK (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate left and right ventricular functions at rest by pulsed-wave Doppler and tissue Doppler echocardiography methods in patients with Behçet’s disease (BD) without overt cardiovascular disease, and compare with age and sex matched subjects. Patients and methods: Fifty-four patients with BD (12 males, 42 females; mean age 35±8 years; range 18 to 51 years) without cardiovascular symptoms, and 36 age-matched controls (12 males, 24 females; mean age 33±5 years; range 18 to 47 years) were included. Cardiac functions were evaluated by conventional and tissue Doppler echocardiography. Results: Although conventional indices of left ventricular systolic function were similar in both groups, mitral annular systolic velocity was lower (p<0.001) and myocardial performance index was higher (p<0.001) in patients with BD compared to the controls. As an early diagnostic marker of contractile dysfunction, intra- and interventricular dyssynchrony were more common in patients with BD. In addition, mitral E/A ratio of <1 was more common (p<0.001), isovolumic relaxation time (p=0.032) and mitral deceleration time (p=0.037) were longer in patients with BD compared to the control group. All Doppler parameters of right ventricular function were impaired in patients with BD. Atrial septal aneurysm was more frequent in patients with BD than controls (p=0.007). Conclusion: Right ventricular and left ventricular function is impaired in patients with BD. Clinically silent cardiovascular involvement can be detected early by tissue Doppler echocardiography even in asymptomatic patients with BD.